2016
DOI: 10.1242/jcs.179036
|View full text |Cite
|
Sign up to set email alerts
|

Conditional mutation of Smc5 in mouse embryonic stem cells perturbs condensin localization and mitotic progression

Abstract: Correct duplication of stem cell genetic material and its appropriate segregation into daughter cells are requisites for tissue, organ and organism homeostasis. Disruption of stem cell genomic integrity can lead to developmental abnormalities and cancer. Roles of the Smc5/6 structural maintenance of chromosomes complex in pluripotent stem cell genome maintenance have not been investigated, despite its important roles in DNA synthesis, DNA repair and chromosome segregation as evaluated in other model systems. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 71 publications
3
48
2
Order By: Relevance
“…In the case of SMC6 , however, we were unable to generate any CRISPR-modified cells. Previous papers show that ablation of SMC6 resulted in embryonic lethality in mice [26] and that conditional knockout of SMC5 in mouse embryonic stem cells induced apoptosis [28]. Therefore, the failure to generate SMC6 -deprived clones in our studies most likely reflects that SMC6 is also essential for cell survival in humans.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the case of SMC6 , however, we were unable to generate any CRISPR-modified cells. Previous papers show that ablation of SMC6 resulted in embryonic lethality in mice [26] and that conditional knockout of SMC5 in mouse embryonic stem cells induced apoptosis [28]. Therefore, the failure to generate SMC6 -deprived clones in our studies most likely reflects that SMC6 is also essential for cell survival in humans.…”
Section: Discussionmentioning
confidence: 69%
“…NSMCE2 has also been shown to be essential for mouse development and it can suppress cancer and aging by limiting recombination and facilitating chromosome segregation [27]. In line with these studies, a recent paper describes that depletion of SMC5 in mouse embryonic stem cells led to accumulation of cells in G2 and subsequent mitotic failure and apoptosis [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Since Nestin is expressed in progenitor cells of tissues other than neural, some degree of DNA excision was also observed in kidneys and muscles in our samples ( Figure 1B and Figure 1-figure supplement 1A) (Bernal et al, 2018;Sakairi et al, 2007). SMC5 depletion in the developing mouse cortex resulted in a significant increase in cleaved caspase 3 (CASP3)-positive cells in Smc5 cKO compared to controls in both, E13.5 and E16.5 cortices ( Figure We have previously shown that the depletion of SMC5 in mESCs causes chromosome segregation defects during mitosis (Hwang et al, 2017;Pryzhkova and Jordan, 2016). Thus, we analyzed VZ and SVZ mitotic progenitors in cortical sections of E13.5 and E16.…”
Section: Smc5 Cko Causes Neurodevelopmental and Sensorimotor Defects mentioning
confidence: 97%
“…Although the function of this complex is mostly outside of mitosis, its impact on chromosome organization also influences mitotic chromosome morphology. Direct evidence for the importance of SMC5/6 to mitotic chromosome assembly is based on observations that human cells lacking SMC6 or SMC5 display defective chromosome morphology and faulty mitotic localization of topoisomerase II or condensin [ 112 , 113 ]. Whether or not the SMC5/6 complex is present on mitotic chromatin has been controversial.…”
Section: Regulation Of Topoisomerase II Activity: Guidance By the mentioning
confidence: 99%
“…Whether or not the SMC5/6 complex is present on mitotic chromatin has been controversial. Whereas some studies reveal it is virtually absent from mitotic chromosomes [ 112 ], others report an enrichment at pericentromeric regions, at the chromosomal axis, and at DNA bridges caused by topoisomerase II inhibition [ 113 , 114 ]. It thus remains unclear if this complex is actively shaping chromatin during mitosis.…”
Section: Regulation Of Topoisomerase II Activity: Guidance By the mentioning
confidence: 99%